1990
DOI: 10.1017/s0952523800000754
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of quisqualate/ kainate and NMDA receptors to excitatory synaptic transmission in the rat's visual cortex

Abstract: Actions of antagonists for excitatory amino-acid (EAA) receptors on extracellularly and intracellularly recorded responses of layer II/III cells to electrical stimulation of the underlying white matter were studied in a slice preparation of rat's visual cortex. Antagonists used were 2-amino-5-phosphonovalerate (APV) and 6-cyano-7-nitroquinoxaline-2,3-dione (CNQX), which are selective antagonists for EAA receptors of N-methyl-D-aspartate (NMDA) and quisqualate/kainate (non-NMDA) type, respectively. In extracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 57 publications
2
14
0
Order By: Relevance
“…Consistent with previous reports (Collingridge and Lester, 1989; Nishigori et al, 1990; Daw et al, 1993), we found that AMPA receptor activation was responsible for most significant neural transmission, as its antagonist CNQX alone essentially abolished photostimulation-evoked VSD responses and blocked translaminar propagation across V1 locations. In addition, the NMDA receptor antagonist, CPP preferentially suppressed photostimulation-evoked excitatory propagation at the peak phase, which fits with the slower kinetics but longer durations of NMDA receptor activation (Collingridge and Lester, 1989; Daw et al, 1993) and is consistent with the earlier report that NMDA receptors may differentially contribute to generation of neuronal action potentials or EPSPs with slow onsets in rat barrel cortex in vivo and in rat visual cortex in vitro (Nishigori et al, 1990; Armstrong-James et al, 1993). Therefore, NMDA receptor activation is important in modulating visual cortical circuit excitability in the mouse.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous reports (Collingridge and Lester, 1989; Nishigori et al, 1990; Daw et al, 1993), we found that AMPA receptor activation was responsible for most significant neural transmission, as its antagonist CNQX alone essentially abolished photostimulation-evoked VSD responses and blocked translaminar propagation across V1 locations. In addition, the NMDA receptor antagonist, CPP preferentially suppressed photostimulation-evoked excitatory propagation at the peak phase, which fits with the slower kinetics but longer durations of NMDA receptor activation (Collingridge and Lester, 1989; Daw et al, 1993) and is consistent with the earlier report that NMDA receptors may differentially contribute to generation of neuronal action potentials or EPSPs with slow onsets in rat barrel cortex in vivo and in rat visual cortex in vitro (Nishigori et al, 1990; Armstrong-James et al, 1993). Therefore, NMDA receptor activation is important in modulating visual cortical circuit excitability in the mouse.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, the intense immunostained puncta in layer IVC forms a pattern of alternating intensely stained stripes and poorly stained stripes that can be related to geniculocortical afferent terminations (Hubel and Wiesel, 1972;Hendrickson et al, 1978;DeFelipe and Jones, 1991), clusters of dendrites (Peters and Sethares, 1991), and glutamate immunoreactive processes (Carder and Hendry, 1994). This hypothesis is also supported by a large body of literature indicating that excitatory neurotransmission at thalamocortical synapses is primarily mediated by AMPA receptors (Hagihara et al, 1988;Shirokawa et al, 1989;Fox et al, 1989Fox et al, , 1992Nishigori et al, 1990;Gil and Amitai, 1996). Despite the fact that geniculocortical afferent terminals may represent less than 20% of the asymmetrical synapses in layer IVC (Garey and Powell, 1971;Tigges and Tigges, 1979;Peters et al, 1994), physiological evidence indicates that thalamic input plays an essential role in driving cortical cells (Tanaka, 1983;Ferster et al, 1996).…”
Section: Ampa Subunit Organization In Macaque V1mentioning
confidence: 64%
“…AMPA receptors (Petralia and Wenthold, 1992) are especially associated with thalamocortical (Tsumoto et al, 1986;Shirokawa et al, 1989;Armstrong-James et al, 1993) and commissural synaptic connections in adult cortex (Tsumoto, 1990), whereas NMDA receptors are especially associated with corticocortical connections (Thomson, 1986;Jones and Baughman, 1988;Shirokawa et al, 1989;Sutor and Hablitz, 1989;Nishigori et al, 1990;Larson-Prior et al, 1991;Kawaguchi, 1992;Nicoll et al, 1992;. NMDA-mediated excitatory postsynaptic potentials are evoked in layer II/III neurons with less intense stimuli than those in layer IV neurons (Thomson, 1986), and layer II and III neurons have a higher sensitivity to NMDA and amino-5-phosphonovaleric acid (APV) than do layer IV, V, and VI neurons (Fox and Armstrong-James, 1986;Fox et al, 1989Fox et al, , 1990Shirokawa et al, 1989).…”
Section: Implications For Cortical Connectivity and Plasticitymentioning
confidence: 99%